PERANCANGAN BUKU PEDOMAN PELAKSANAAN WIRID REMAJA MASJID DI DESA TANJUNG PUCUK JAMBI - Tri Winanda; Oktarina Yusra (EDUCATIONAL JOURNAL : General and Specific Research, 2023)
This research is motivated by a number of problems that the authors found in the implementation of Wirid Youth Mosque activities in Tanjung Pucuk Jambi Village, to be precise at the al-Muhlisin Mosque. The mosque's youth wirid activities have not been carried out properly, the implementation of activities only uses traditional implementation, meaning that it is only carried out in accordance with the knowledge of the mosque youth wirid supervisor without any guidelines that must be followed, due to the absence of guidelines to follow for carrying out mosque youth wirid activities, mosque youth wirid supervisors often make confusion in implementing mosque youth wirid activities. In each mosque youth wirid activity there are only lecture activities conducted by the supervisor, so that the mosque youth wirid activities are not very good in front of the participants or students who take part in the mosque youth wirid activities. The purpose of this research is to produce a product in the form of a guidebook for the implementation of mosque youth wirid that can be used and used in general in Tanjung Shoots Jambi village, especially at the Al-Muhlisin mosque which is valid, practical, and effective for use in mosque youth wirid activities. The type in this research is by using the Research and Development research method which means research and development. The model used in this research is 4-D, define, design, develop and dissemination. Based on the results of the research that has been carried out, it can be concluded that the resulting mosque youth wirid guidebook can later be used and useful so that it is appropriate to be used as a guide for coaches, teachers and students in mosque youth wirid activities, especially at the Al-Muhlisin Tanjung Shoots Mosque, Jambi. The results of the validation trial by experts on the wirid youth mosque manual can be in the (valid) category with an average value of 0.79. In the practicality test of the mosque's youth wirid manual, the results showed that it had a level of practicality (very practical), with a value of 94%, while the results of the effectiveness test had a level (medium effectiveness) with a value of 0.4.